2022
DOI: 10.1002/jeq2.20332
|View full text |Cite
|
Sign up to set email alerts
|

Culturable antibiotic‐resistant fecal coliform bacteria in soil and surface runoff after liquid dairy manure surface application and subsurface injection

Abstract: Land application of manure, while beneficial to soil health and plant growth, can lead to an overabundance of nutrients and introduction of emerging contaminants into agricultural fields. Compared with surface application of manure, subsurface injection has been shown to reduce nutrients and antibiotics in surface runoff. However, less is known about the influence of subsurface injection on the transport and persistence of antibiotic‐resistant microorganisms. We simulated rainfall to field plots at two sites (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…From Table 2, we note that the total number of coliform bacteria in the soil is also high, and the reason may be the use of organic fertilizers, poor reclamation of agricultural lands, or overgrazing and animal waste (Hilaire et al, 2022). While the irrigation water samples were less contaminated with coliform bacteria, because the water was taken from pumps that draw water from the river, meaning that the water is running and not static, so the percentage of contamination was less (Eissa et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…From Table 2, we note that the total number of coliform bacteria in the soil is also high, and the reason may be the use of organic fertilizers, poor reclamation of agricultural lands, or overgrazing and animal waste (Hilaire et al, 2022). While the irrigation water samples were less contaminated with coliform bacteria, because the water was taken from pumps that draw water from the river, meaning that the water is running and not static, so the percentage of contamination was less (Eissa et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A balance between livestock health and reducing global antimicrobial resistance must be reached. One potential way to minimize antibiotic resistance propagation is to implement manure management strategies that maximize nutrient utilization but minimize the direct contract between manure and crops. Manure injection strategies, in which manure is placed below the ground surface in shallow (12–25 cm deep) slits, are now known to minimize the associated risks of manure land application such as surface runoff of excess nutrients and transport of veterinary antibiotics and ARB. , …”
Section: Introductionmentioning
confidence: 99%
“…Subsurface injection has proven to be particularly effective at reducing transport of AREs into surface runoff after heavy rainfall when compared to surface application of manure . Le et al showed reduction of specific antimicrobials, whereas Hilaire et al showed reduction of sulfamethazine-, tetracycline-, and erythromycin-resistant Escherichia coli ( E. coli ) . Compared to manure surface application, implementation of subsurface manure injection resulted in 47%–88% reduction for sulfamerazine, chlortetracycline, pirlimycin, and tylosin and 227–593 times reduction for sulfamethazine-, tetracycline-, and erythromycin-resistant Escherichia coli ( E. coli ) in surface runoff .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations